2017
DOI: 10.4103/1008-682x.174854
|View full text |Cite
|
Sign up to set email alerts
|

DNA fragmentation in two cytometric sperm populations: relationship with clinical and ultrasound characteristics of the male genital tract

Abstract: We investigated whether DNA fragmentation in two cytometric sperm populations (PIdimmer and PIbrighter) with different biological characteristics and clinical relevance is related to clinical and color-Doppler ultrasound (CDUS) parameters of the male genital tract. One hundred and sixty males of infertile couples without genetic abnormalities were evaluated for clinical, scrotal, and transrectal CDUS characteristics, presence of prostatitis-like symptoms (with the National Institutes of Health-Chronic Prostati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Benign prostatic hyperplasia (BPH) is a reproductive disorder of men and dogs [1,2], with high prevalence in aged males [3,4]. The etiology of BPH is related to a hormonal imbalance between testosterone and estrogen and an increased activity of 5α-reductase, leading to higher dihydrotestosterone (DHT) concentrations [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benign prostatic hyperplasia (BPH) is a reproductive disorder of men and dogs [1,2], with high prevalence in aged males [3,4]. The etiology of BPH is related to a hormonal imbalance between testosterone and estrogen and an increased activity of 5α-reductase, leading to higher dihydrotestosterone (DHT) concentrations [5].…”
Section: Introductionmentioning
confidence: 99%
“…Impaired spermatogenesis is often observed [7], which may affect sperm DNA integrity [8,9]. Sperm DNA damage related to BPH was previously described in dogs [3] and men [4], albeit not yet completely elucidated. It is suggested that biochemical modifications of the prostatic fluid play an important role on sperm damage.…”
Section: Introductionmentioning
confidence: 99%
“…SDF can originate in both testicles and during sperm transit in the genital tract [7]. Increased levels of seminal apoptotic M540 bodies suggest disruption of spermatogenesis and testicular abnormalities [8].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that viable, DNA fragmented spermatozoa are cells where DNA damage developed more recently respect to the ejaculation (28), these results suggest that oxidative stress acts later in sperm's life, most likely during transit in the male genital tract, whereas apoptotic damage occurs earlier, mainly at testicular level. A recent clinical study (36) seems to confirm such hypothesis revealing that sDF in unviable spermatozoa is associated mainly with the presence of ultrasound signs of testicular abnormalities, whereas the DNA fragmented sperm population containing viable spermatozoa was mostly associated with clinical and ultrasound alterations of the prostate and of seminal vesicles, likely due to inflammatory statuses. There is also evidence that DNA damage may occur after ejaculation during in vitro incubations (3739) or because of in vitro manipulation during sperm selection for ARTs (33, 34, 40).…”
Section: Introductionmentioning
confidence: 77%